Quaternary Aqueous Biphasis Mixture For Enzyme Extraction From Banana - Chen, Yi (Universiti Sains Malaysia, 2022)
Enzyme extraction by using various solvent such as ionic liquids was used in the past. Recently, a green solvent which is deep eutectic solvents (DESs) have gained attention from the community because of its simplicity and the affordable cost in extracting the protein with aqueous two-phase system (ATPS). Through this study, four choline chloride-(HBDs) DES with different molar ratio was studied to extract bovine serum albumin (BSA) and protein in banana. Molar ratio for choline chloride: glycerol (ChCl: Gly) at 1:2, choline chloride: lactic acid (ChCl: Lac) at 1:2, choline chloride: urea (ChCl: Urea) at 1:2 and choline chloride: glucose (ChCl: Glu) at 2:1 will form a clear and transparent homogenous mixture at room temperature. With the formation of DES, the effect of the concentration and volume for polyethylene glycol (PEG), sodium sulphate (Na2SO4) and DES were studied. 1000 μL of 1.0 M Na2SO4, 1000 μL of PEG and 100 μL of DES was chosen because it took the shortest time for the formation of two-phase which is 97.33 mins. A calibration curve of different DES with BSA reagent which the corrected absorbance against protein concentration is then plotted. The protein concentration of banana was compared with the calibration curve with different DES. The results showed ATPS with ChCl: Lac (top phase) extracted the most protein which is 3678.33 μg/ml with the highest extraction efficiency of 89.60 %. This might be affected by the functional group of the HBDs, and low viscosity of banana crude extract interacts with the DES where the hydrogen bonds affect the mobility of free molecules within the system such as the movement of protein within the solvent leads to fast mass transfer of protein.